Factors Influencing E-Commerce Adoption In The United Republic Of Tanzania - Koyi, Sebastian Paul (2008)
This study is focusing on the factors influencing e-commerce adoption in Tanzania. Beside this it also examines factors that hinder e-commerce adoption in Tanzania.